Rezension von: Wahl, Joachim; Luig, Alexander, Kaelble - Fritz, Gerhard (Backnanger Jahrbuch, 2000)
Joachim Wahl und Alexander Luig: Kaelble. Lastwagen und Zugmaschinen. Brilon: Podszun-Motorbücher, 1999, 214 S.